Marketing development strategy of tempe home industry in Sidenreng Rappang Regency - Rustan Rustan; Nuraeni Kadir; Muhammad Toaha (Institute of Computer Science (IOCS), 2023)
Sidenreng Rappang Regency is one of the tempe home industry production centres. This research aims to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, and then formulate and set priorities for the marketing development strategy of the tempe home industry in Sidenreng Rappang Regency. This research was analysed using the help of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to answer strategic factors that become strengths and weaknesses as well as opportunities and threats, followed by a SWOT matrix analysis to formulate and set priorities for industrial marketing development strategies. Tempe home in Sidenreng Rappang Regency. The results of the study show that internal and external factors are the strengths and weaknesses as well as opportunities and threats in developing the marketing of the tofu industry, so several alternative strategies can be considered, including product diversification and market expansion strategies, strategies for increasing human resources and product innovation, strategies to strengthen differentiation and collaboration as well as strategies to increase competence and diversify sources of raw materials.